2008
DOI: 10.1007/s00436-008-1092-3
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of two strains of mice to the infection with Schistosoma mansoni: Parasitological and biochemical studies

Abstract: In this article, two strains of mice BALB/C and C57 were infected with Egyptian strain of Schistosoma mansoni. BALB/C mice appeared to harbor fewer parasites than did C57 mice. The hepatic and intestinal tissues of C57 mice were loaded with more eggs than that of BALB/C mice. Regardless the strain of mice, the number of eggs per gram of liver tissues was higher than in the intestinal tissues. Some biochemical parameters were measured in the liver of infected and non-infected mice; a significant decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
4
11
1
Order By: Relevance
“…The male worms' proportion was higher than the female worms' proportion in both treated and non-treated mice; this was correlated with the meta-analytical finding of Boissier and Moné (2001) and Bin Dajem et al (2008) in their studies on the susceptibility of BALB/C and C57 to S. mansoni infection. Boissier and Moné (2001) observed a significant positive relationship between S. mansoni worm burden and male worms' proportion in four host models: rats, mice, hamsters and monkeys.…”
Section: Discussionsupporting
confidence: 56%
“…The male worms' proportion was higher than the female worms' proportion in both treated and non-treated mice; this was correlated with the meta-analytical finding of Boissier and Moné (2001) and Bin Dajem et al (2008) in their studies on the susceptibility of BALB/C and C57 to S. mansoni infection. Boissier and Moné (2001) observed a significant positive relationship between S. mansoni worm burden and male worms' proportion in four host models: rats, mice, hamsters and monkeys.…”
Section: Discussionsupporting
confidence: 56%
“…Using C57BL/6 strain of mice is in accordance with previous studies which showed that this strain was more susceptible to the infection with Egyptian strain of S. mansoni than BALB/c mice strain (Bin Dajem et al 2008), and is known to respond better to UV-irradiated cercariae (Murrell et al 1979;Richter et al 1993;Mountford et al 2001). In addition, Incani et al (2001) reported that the strain of the host appeared to influence the susceptibility to infection, the fecundity, and the percentage of eggs distributed in liver and in intestine during chronic stage of infection.…”
Section: Discussionsupporting
confidence: 84%
“…Previous study showed that C57BL/6 strain of mice was more susceptible to the infection with Egyptian strain of S. mansoni than BALB/c mice strain (Bin Dajem et al 2008) and is known to respond better to UV-irradiated cercariae (Murrell et al 1979;Richter et al 1993;Mountford et al 2001). We intentionally used C57BL/6 mice because they seem to be high responders than BALB/c mice who showed moderate response as reported by Mountford et al (2001).…”
Section: Discussionmentioning
confidence: 83%